PWE-095 Serum micronutrients levels are maintained post-intestinal transplant in keeping with graft function. (17th June 2017) - Ravindran, RP; McGuire, J; Patel, M; Loo, L; Patel, M; Vokes, L; Holdaway, L; Smith, A; Vrakas, G; Reddy, S; Friend, P; Shine, B; et al.
Abstract : Introduction: Chronic intestinal failure is defined by the lack of absorption of micronutrients, macronutrients or water requiring intravenous support. The absorptive capacity of the gut is determined by length of gut present in continuity, enteric adaptation and speed of transit. Frequently patients require intravenous micronutrient support. Following intestinal transplant (ITx) the graft is able to absorb both micro and macronutrients such that parenteral nutrition (PN) is no longer required. We studied transplanted patients in a single centre to assess the absorption of micronutrients. Method: This was a retrospective analysis of a prospective database. Results were taken from patients being assessed for ITx, then at 3 monthly intervals, and then yearly. Data are inclusive of results either side of the specified timepoint. Data were analysed on Prism using one-way ANOVA and Tukey multiple comparisons test. Data reported as mean ±95% confidence interval. Results: 34 patients received 35 transplants. Mean age was 41.9y (range 23–73). M/F: 22:14. Median follow up was 774d (range 16–3029). Indications included Crohn's disease (7/36, 19%), intra-abdominal desmoids (4/36, 11%), visceral neuromyopathy (5/36, 14%), vascular ischaemia (6/36, 17%), radiation enteritis (2/36, 6%), NET (1/34, 3%), pseudomyxoma peritonii (6/36, 17%) and other (5/36, 13%). Zinc, folic acid, B12, Vitamin A and Vitamin D were significantly different using one way ANOVA: Zinc (p<0.0001) with significant Tukey for pre-ITx (16.9±1.07) vs. 12m (14.2±1.2, p<0.05), vs. 24m (13.5±1.5, p<0.05), vs. 36m (12.9±1.4, p<0.005) and vs. 48m (13.2±1.2, p<0.005); Folic acid (p=0.0006) with significant Tukey for pre-ITx (10.1±0.9) vs. 3m (6.6±1.0, p<0.05), vs. 6m (5.71±1.3, p<0.05); and between 3m vs. 24m (11.7±2.5, p<0.005) and 6m vs. 24m (p<0.005); B12 (p=0.0349) with significant Tukey for 6m (883.2±202.8) vs. 24m (555.8±121.3); Vitamin A (p<0.0001) with significant Tukey for pre-Tx (1.87±0.41) vs 3m (3.27±0.56, p<0.001), 3m vs. 24m (1.79±0.32, p<0.001) and vs. 48m (2.22±0.34, p<0.05), 6m (2.80±0.55) vs. 24m (p<0.05); Vitamin D (p=0.0469) without significant Tukey for any timepoints. Conclusion: Observing micronutrient changes aids our understanding of transplanted graft function and nutritional intake. The reduction in zinc, folate and B12 is perhaps more physiological than clinically significant, as the levels were within the normal range and may reflect over-treatment when on PN, though it is interesting to observe folate rising back to a higher level after 6m. It is reassuring to observe that the ITx is not deleterious to micronutrient metabolism. Disclosure of Interest: None Declared